Isatuximab-pomalidomide-dexamethasone versus pomalidomide-dexamethasone in patients with relapsed and refractory multiple myeloma: final overall survival analysis - Richardson, Paul G; Perrot, Aurore; Miguel, Jesus San; Beksac, Meral; Spicka, Ivan; Leleu, Xavier; Schjesvold, Fredrik; Moreau, Philippe; Dimopoulos, Meletios A; Huang, Shang-Yi; Minarik, Jiri; Cavo, Michele; et al. (Haematologica, 2024)
The primary and prespecified updated analyses of ICARIA-MM (clinicaltrial gov. Identifier: NCT02990338) demonstrated improved progression-free survival (PFS) and a benefit in overall survival (OS) was reported with the addition of isatuximab, an anti-CD38 monoclonal antibody, to pomalidomide-dexamethasone (Pd) in patients with relapsed/refractory multiple myeloma. Here, we report the final OS analysis. This multicenter, randomized, open-label, phase III study included patients who had received and failed ≥2 previous therapies, including lenalidomide and a proteasome inhibitor. Between January 10, 2017, and February 2, 2018, 307 patients were randomized (1:1) to isatuximab-pomalidomide-dexamethasone (Isa-Pd; N=154) or Pd (N=153), stratified based on age (<75 vs. ≥75 years) and number of previous lines of therapy (2-3 vs. >3). At data cutoff for the final OS analysis after 220 OS events (January 27, 2022), median follow-up duration was 52.4 months. Median OS was 24.6 months (95% confidence interval [CI]: 20.3-31.3) with Isa-Pd and 17.7 months (95% CI: 14.4- 26.2) with Pd (hazard ratio=0.78; 95% CI: 0.59-1.02; 1-sided P=0.0319). Despite subsequent daratumumab use in the Pd group and its potential benefit on PFS in the first subsequent therapy line, median PFS2 was significantly longer with Isa-Pd versus Pd (17.5 vs. 12.9 months; log-rank 1-sided P=0.0091). In this analysis, Isa-Pd continued to be efficacious and well tolerated after follow-up of approximately 52 months, contributing to a clinically meaningful, 6.9-month improvement in median OS in patients with relapsed/refractory multiple myeloma.
Keywords: dospělí; Drug Resistance, Neoplasm; Recurrence; Female; thalidomid; Thalidomide; Adult; výsledek terapie; ženské pohlaví; lidé; Survival Analysis; mnohočetný myelom; recidiva; chemorezistence; Treatment Outcome; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Male; Aged; dexamethason; Dexamethasone; analýza přežití; lidé středního věku; humanizované monoklonální protilátky; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; Middle Aged; Humans